Before and After AGENCY - The Agency Research Group (Footprint)
This article offers a critical review of the conference AGENCY (November 2008), written by ‘The Agency’, a research group based in the School of Architecture at the University of Sheffield, where the conference was held. It was hoped that the submissions to the conference would energise the relationships between the humanities, the architectural profession, and society.